Analysis Of The Political Oligarchy DPR Of Indonesia During The Jokowi Administration (2019-2024) - Tsalitsa Haura Layyina; Mohammad Rafatta Umar; Muhammad Akbar Rahmadhani; Cindy; Ridwan (PT ARRUS Intelektual Indonesia, 2024)
This study aims to analyze the impact of political oligarchy on the legislative process and the quality of democracy in the Indonesian House of Representatives (DPR) during President Jokowi's administration (2019–2024). Employing a qualitative research method based on library studies, the research explores the relationship between political elites and large business groups in shaping public policies. The findings indicate that oligarchy significantly influences policy formation, exemplified by the revisions to the KPK Law, the Minerba Law, and the Omnibus Job Creation Law. These policies often favor elite groups over the broader public. The study also reveals that oligarchic dominance reduces transparency, accountability, and public participation in the legislative process, posing a threat to democratic norms. Furthermore, politicians' reliance on financial support from elite groups reinforces the oligarchy’s role in determining national policy directions. Based on these findings, it is recommended to enhance legislative transparency, strengthen public oversight, and develop inclusive mechanisms for public participation to improve the quality of democracy in Indonesia.